Treatment of Radiation Bone Injury with Transplanted hUCB-MSCs via Wnt/β-Catenin. (28th November 2021) - Zhang, Yufeng; Deng, Huaxin; Yang, Zhiqiang; Chen, Zhe; Zhang, Sheng; Zhu, Yufan; Yang, Min; Zhong, Houcheng; Zhou, Fuling; Xie, Yuanlong; Cai, Lin
Abstract : Radiation-induced bone injury (RIBI) is one of the complications after radiotherapy for malignant tumors. However, there are no effective measures for the treatment of RIBI in clinical practice, and the mechanism of RIBI is unclear. We use a single high-dose ionizing radiation (6Gy) to analyze the effect of radiotherapy on osteoblast function. Human umbilical cord blood mesenchymal stem cells (hUCB-MSCs) were cocultured with irradiated osteoblasts to examine their therapeutic effects and mechanisms on osteoblast injury. The hUCB-MSC transplantation mouse model is used to confirm the in vivo role of hUCB-MSC treatment in radiation bone injury. Western blot analysis, qRT-PCR, immunohistochemistry, and immunofluorescence staining were used to analyze gene expression and angiogenesis. The apoptosis and migration of osteoblasts were measured by Hoechst staining, scratch test, and transwell. The differentiation of osteoblasts was measured by ALP and Alizarin red staining and transmission electron microscopy. The bone-related parameters of mice were evaluated by micro-CT analysis. We found that radiation can damage the DNA of osteoblasts; induce apoptosis; reduce the differentiation, migration, and adhesion of osteoblasts, leading to lipogenesis of bone marrow mesenchymal stem cells (BMSCs) and reducing the source of osteoblasts; and increase the number of osteoclasts in bone tissue, while MSC treatment prevents these changes. Our results reveal the inhibitory effect of radiation on osteoblast function. hUCB-MSCs can be used as a therapeutic target for the development of new therapeutic strategies for radiotherapy of bone injury diseases.